Integration of Customary Law and Ethnoecological Concepts in Supporting Sustainable Agricultural Practices - Yohanes Kamakalula; Yunita Palinggi; Obadja Andris Fenetiruma (PT. Anagata Sembagi Education, 2025)
This study aims to describe the role of customary law and the concept of ethnoecology in supporting sustainable agricultural practices, while analyzing their integration as a model of agriculture based on local wisdom. The study used a qualitative approach with field study and literature study methods. Primary data were obtained through in-depth interviews, participatory observation, and focus group discussions with customary leaders and farmers, while secondary data were obtained from customary documents and related literature. Data analysis was conducted using the interactive model of Miles & Huberman through data reduction, data presentation, and drawing conclusions through source triangulation. The results show that customary law plays a role as a local regulation in agricultural management, while ethnoecology exists as a technical practice that maintains ecosystem balance. The integration of the two forms a sustainable agricultural system, not only increasing productivity but also maintaining environmental sustainability and strengthening social solidarity. This study confirms that customary law not only has social value but is also an ecological instrument relevant to modern sustainable agriculture.